Ultraviolet Radiation and Melanomagenesis: From Mechanism to Immunotherapy - Sun, Xiaoying; Zhang, Na; Yin, Chengqian; Zhu, Bo; Li, Xin (Frontiers in Oncology, 2020)
Melanoma is the deadliest form of skin cancer, and nearly 90% of melanomas are believed to be caused by ultraviolet radiation (UVR), mainly from sunlight. UV radiation induces DNA damage, forming products such as cyclobutane pyrimidine dimers (CPD), and 6-4-pyrimidone photoproducts (6-4PP) in a wavelength-dependent manner, and causes oxidative DNA damage. These DNA lesions lead to DNA mutations and contribute to the formation of melanoma. In this review, we discuss the protective role of melanocytes against UV-induced DNA damage and how genetic variations, including those in p53 and melanocortin‐1 receptor (MC1R), or epigenetic histone modifications in melanocytes result in a tendency towards melanoma. We also provide a summary of prevention and treatment strategies against melanoma, including the most recent immunotherapies. Collectively, this work contributes to the understanding of the molecular pathogenesis of UV-induced melanoma.